Hydrographical time series data of the littoral zone of Kongsfjorden, Svalbard 2024 - Fischer, Philipp; Lienkämper, Miriam; Schwanitz, Max (PANGAEA, 2025)
The dataset contains temperature, salinity, oxygen saturation, chlorophyll a and turbidity data from the AWIPEV underwater observatory from the year 2024 in a temporal resolution of 1 hour. The cabled observatory is located in 12m water depth and comprises single or multiple sensors for a specific parameter (see https://www.awi.de/en/science/biosciences/shelf-sea-system-ecology/main-research-focus/cosyna/underwater-node-spitsbergen.html). For a detailed description of the data see associated metadatafile metadata_svulobs_2024_hydrography.pdf